2016
DOI: 10.1016/j.wjorl.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Advancing theranostics with tumor‐targeting peptides for precision otolaryngology

Abstract: Worldwide, about 600,000 head and neck squamous cell carcinoma (HNSCC) are detected annually, many of which involve high risk human papilloma virus (HPV). Surgery is the primary and desired first treatment option. Following surgery, the existence of cancer cells at the surgical margin is strongly associated with eventual recurrence of cancer and a poor outcome. Despite improved surgical methods (robotics, microsurgery, endoscopic/laparoscopic, and external imaging), surgeons rely only on their vision and touch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
(88 reference statements)
1
1
0
Order By: Relevance
“…11 , the cell viability of the NGO-PEG-HN-1 group is nearly 100% in three kinds of cells. It is indicated that the NGO-PEG is relatively safe and non-toxic to the cells, which is consistent with the previous reports 45 49 . For CAL-27 and SCC-25 cells, it was not difficult to see from Fig.…”
Section: Resultssupporting
confidence: 92%
“…11 , the cell viability of the NGO-PEG-HN-1 group is nearly 100% in three kinds of cells. It is indicated that the NGO-PEG is relatively safe and non-toxic to the cells, which is consistent with the previous reports 45 49 . For CAL-27 and SCC-25 cells, it was not difficult to see from Fig.…”
Section: Resultssupporting
confidence: 92%
“…Small peptides can have equally strong affinity and specificity for targets, faster pharmacokinetics, and are less expensive than antibodies to scale up and develop [12,13,14]. Peptides based upon cyclic arginine-glycine-aspartate (RGD) have been identified that target integrins overexpressed on the surface of human HNSCC cells.…”
Section: Introductionmentioning
confidence: 99%